A Short Review on Microglia in Neurodegenerative Disorders: An Overview of Natural Products in the Treatment of Neurodegenerative Disease by Targeting Arginase 1 - Ahamed, Mohomed Faizal Umair; Sivapragasam, Gothai; Appan, Nanthini Sridewi (International Journal of Pharmaceutical Investigation, 2025)
This review offers an overview of the crucial role microglia play in neurodegenerative disorders such as Alzheimer's, Parkinson's and Huntington's diseases. It also delves into the therapeutic potential of natural products targeting Arginase-1 and L-arginine for treating these conditions. As key immune cells in the brain, microglia significantly contribute to the onset and progression of neuroinflammation, which is closely associated with neurodegeneration. The paper elucidates the intricate interplay between microglial activation, neuroinflammation and the development and progression of neurodegenerative diseases. This review primarily examines the shift of microglial polarization from a pro-inflammatory (M1) to an anti-inflammatory (M2) state, highlighting it as a promising therapeutic approach for treating neurodegenerative diseases. Specifically, the regulation of Arginase-1 and its substrate, L-arginine, within microglia presents a novel avenue for intervention. The review highlights the potential of natural products such as resveratrol, piceatannol, epicatechin, curcumin, sulforaphane, flavonoids and cannabidiol, ginsenosides in influencing microglial function by targeting Arginase-1 and L-arginine metabolism. By targeting Arginase-1, natural products have shown promise in modulating microglial activation and shifting the balance towards an anti-inflammatory phenotype, thereby mitigating neuroinflammation and subsequent neurodegeneration. Moreover, the review underscores the importance of comprehending the molecular processes that drive the effects of these natural products. on microglial function, particularly their impact on Arginase-1 and L-arginine metabolism. In conclusion, this review emphasizes the therapeutic potential of natural products targeting Arginase-1 and L-arginine in the treatment of neurodegenerative diseases by modulating microglial activation and neuroinflammation.
Keywords: Arginase-1; Microglia; Neurodegenerative Diseases